PEMBANGUNAN EKONOMI LOKAL DI ERA OTONOMI DAERAH - Moehaditoyo, Srie Hartutie (DiE: Jurnal Ilmu Ekonomi dan Manajemen, 2009)
Past experience on the economic crisis the important priority agenda is recovery sustainability and effective economic the implementative whose relevance on region autonomy is the pattern of citizen economic development.The short term priority of economic national development after economic crisis focused on the faster of economic recovery with citizen empowerment, and several programs for anticipated the problem of hegher poverty and unemployment on the economic crisis.The approach of citizen empowerment activity in small business enterprise must be focused to relevance implementation. Local government is designer of strategic economic sector emporment through build of modelling with appropriate.The position of micro, small and medium business is very important because this endure depressed in real business economic sector government is institution whose responsive to captive, development and empowerment.Economic development strategy used primary concept of local autonomy with accomodate citizen economic development concepts. Economic activity is business whose done by citizenship in the self management of resources, called micro, small, and medium business enterprises. Keyword :    Strategic of business – Empowerment of citizenship – economic development.